Literary Review Of Shalya Nirharan (Removal Of Foreign Bodies) According To Acharya Susruta - Meena, Tarun; Gupta , Rajesh (International Research Journal of Ayurveda & Yoga, 2021)
Acharya Susrutha defined Shalya Tantra as the science that deals with the removal of different kinds of Shalya (foreign body) and application of Yantra, Sastra, Kshara, Agniand Vrana Nidana. In that for Pranashta Shalya (foreign body) Diagnosis and its removal, Acharya had given separate chapters. The intelligent physician after carefully observing the shape of the foreign body, the place of its lodging and deciding the particular instruments to be used, should pull out the foreign body; those which have ears attached and which are difficult to pull out should be removed with appropriate methods, if necessary with the help of other instruments using them with his intelligence: if not pulled out, these are going to produce swelling, ulceration, severe pain, deformities and even death, hence these should be removed by all efforts.